Impact of Pretransplant Bridging Locoregional Therapy for Patients With Hepatocellular Carcinoma Within Milan Criteria Undergoing Liver Transplantation: Analysis of 3601 Patients From the US Multicenter HCC Transplant Consortium. Issue 3 (September 2017) - Agopian, Vatche G.; Harlander-Locke, Michael P.; Ruiz, Richard M.; Klintmalm, Goran B.; Senguttuvan, Srinath; Florman, Sander S.; Haydel, Brandy; Hoteit, Maarouf; Levine, Matthew H.; Lee, David D.; Taner, C. Burcin; Verna, Elizabeth C.; et al.
Abstract : Objective: To evaluate the effect of pretransplant bridging locoregional therapy (LRT) on hepatocellular carcinoma (HCC) recurrence and survival after liver transplantation (LT) in patients meeting Milan criteria (MC). Summary Background Data: Pre-LT LRT mitigates tumor progression and waitlist dropout in HCC patients within MC, but data on its impact on post-LT recurrence and survival remain limited. Methods: Recurrence-free survival and post-LT recurrence were compared among 3601 MC patients with and without bridging LRT utilizing competing risk Cox regression in consecutive patients from 20 US centers (2002–2013). Results: Compared with 747 LT recipients not receiving LRT, 2854 receiving LRT had similar 1, 3, and 5-year recurrence-free survival (89%, 77%, 68% vs 85%, 75%, 68%; P = 0.490) and 5-year post-LT recurrence (11.2% vs 10.1%; P = 0.474). Increasing LRT number [3 LRTs: hazard ratio (HR) 2.1, P < 0.001; 4+ LRTs: HR 2.5, P < 0.001), and unfavorable waitlist alphafetoprotein trend significantly predicted post-LT recurrence, whereas LRT modality did not. Treated patients achieving complete pathologic response (cPR) had superior 5-year RFS (72%) and lower post-LT recurrence (HR 0.52, P < 0.001) compared with both untreated patients (69%; P = 0.010; HR 1.0) and treated patients not achieving cPR (67%; P = 0.010; HR 1.31, P = 0.039), who demonstrated increased recurrence compared with untreated patients in multivariate analysis controlling for pretransplant and pathologic factors (HR 1.32, P = 0.044). Conclusions: Bridging LRT in HCC patients within MC does not improve post-LT survival or HCC recurrence in the majority of patients who fail to achieve cPR. The need for increasing LRT treatments and lack of alphafetoprotein response to LRT independently predict post-LT recurrence, serving as a surrogate for underlying tumor biology which can be utilized for prioritization of HCC LT candidates. Abstract : Supplemental Digital Content is available in the text